An RGS2 3′UTR polymorphism is associated with preeclampsia in overweight women. Issue 1 (December 2016) - Karppanen, Tiina; Kaartokallio, Tea; Klemetti, Miira; Heinonen, Seppo; Kajantie, Eero; Kere, Juha; Kivinen, Katja; Pouta, Anneli; Staff, Anne; Laivuori, Hannele
Abstract Background Preeclampsia is a common and heterogeneous vascular syndrome of pregnancy. Its genetic risk profile is yet unknown and may vary between individuals and populations. The rs4606 3′ UTR polymorphism of the Regulator of G-protein signaling 2 gene (RGS2 ) in the mother has been implicated in preeclampsia as well as in the development of chronic hypertension after preeclampsia. The RGS2 protein acts as an inhibitor of physiological vasoconstrictive pathways, and a low RGS2 level is associated with hypertension and obesity, two conditions that predispose to preeclampsia. We genotyped the rs4606 polymorphism in 1339 preeclamptic patients and in 697 controls from the Finnish Genetics of Preeclampsia Consortium (FINNPEC) cohort to study the association of the variant with preeclampsia. Results No association between rs4606 and preeclampsia was detected in the analysis including all women. However, the polymorphism was associated with preeclampsia in a subgroup of overweight women (body mass index ≥ 25 kg/m2, and < 30 kg/m2 ) (dominant model; odds ratio, 1.64; 95 % confidence interval, 1.10–2.42). Conclusions Our results suggest that RGS2 might be involved in the pathogenesis of preeclampsia particularly in overweight women and contribute to their increased risk for hypertension and other types of cardiovascular disease later in life.